LANGUAGES ACQUISITION AND TEACHING IN KELAPA GADING – NORTH JAKARTA (CASE STUDY TAKEN AT SAINT PETER’S JUNIOR HIGH SCHOOL) - Marudut Bernadtua; Zainal Rafli; Endry Boeriswati (UICELL, 2021)
The application of two or even three languages is very possible for students at the Junior High School level in metropolitan cities because they are usually directed by their families and environment in adapting to challenges. Especially in private schools in big cities, such as Jakarta, learning languages other than Indonesian are also applied, such as learning in Mandarin and also English. The use of languages (English and Mandarin, in addition to Indonesian) at home also needs to be considered, because it really helps the implementation of language acquisition at home and teaching at school. This study aims to examine students' skills in speaking in three languages. This study uses a qualitative method in comparison with the results of the end-of-semester assessment which is the result of the application of the use of the three languages for students, at home and at school. Keywords: Languages Acquisition, Languages Teaching, Saint Peter’s School, North Jakarta